2012
DOI: 10.14250/cement.66.217
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Burning Temperature of Cement Clinker by Adjusting of Mineral Composition

Abstract: KEY WORDS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Authors' previous study has reported that compared to the other components of the clinker, the ferrite phase contributes the most to the sintering of the clinker, and the contributions of the various components to clinker burnability is in the order, C 4 AF>C 3 A>C 2 S>C 3 S (Chabayashi et al, 2012(Chabayashi et al, , 2015. A low-burning-temperature clinker, which sinters at 1,350 • C, which is ∼100 • C lesser than temperature required for the OPC clinker, was produced by increasing the C 4 AF and decreasing the C 2 S proportions while targeting a strength equal to that of the conventional OPC.…”
Section: Introductionmentioning
confidence: 99%
“…Authors' previous study has reported that compared to the other components of the clinker, the ferrite phase contributes the most to the sintering of the clinker, and the contributions of the various components to clinker burnability is in the order, C 4 AF>C 3 A>C 2 S>C 3 S (Chabayashi et al, 2012(Chabayashi et al, , 2015. A low-burning-temperature clinker, which sinters at 1,350 • C, which is ∼100 • C lesser than temperature required for the OPC clinker, was produced by increasing the C 4 AF and decreasing the C 2 S proportions while targeting a strength equal to that of the conventional OPC.…”
Section: Introductionmentioning
confidence: 99%
“…However, the addition of iron can lead to the decomposition of ye'elimite, as a loss of SO 2 already occurs at lower processing temperatures (Puertas et al, 1995;el Khessaimi et al, 2018;Bullerjahn et al, 2020;Yao et al, 2020). It is also reported that the iron content enhances the formation of alite at lower temperatures (Chabayashi et al, 2012;Lu et al, 2018;Hanein et al, 2019).…”
Section: Introductionmentioning
confidence: 99%